Diagnostic accuracy of transient hepatic attenuation differences on computed tomography scans for acute cholangitis in patients with malignant disease. (12th May 2014) - Sugishita, Toshiya; Higuchi, Ryota; Morita, Satoru; Ota, Takehiro; Yamamoto, Masakazu
Abstract Background Few reports have assessed the accuracy of transient hepatic attenuation differences (THAD) in the arterial phase of computed tomography (CT) in diagnosing acute cholangitis (AC). We examined the diagnostic accuracy of THAD in AC in patients with malignant disease. Methods We retrospectively examined the records of 123 consecutive patients (73 men, 50 women; mean age, 69 [range, 43–91] years) who underwent dynamic CT 3 days before biliary drainage for malignant hepatobiliary disease between 2006 and 2011. We examined the diagnostic ability of THAD for AC and assessed the relationship between THAD and AC severity. Results Acute cholangitis was present in 45% of patients. The sensitivity and specificity of THAD for AC were 93% and 39%, respectively. Diffuse, hemi‐hepatic, and segmental THAD for AC were seen in 84%, 4%, and 9%, respectively. In all, 64% of patients were diagnosed with severe AC and 29% with mild AC, depending on the intensity of THAD, but the patterns and degree of intensity of THAD and AC severity were not related. Conclusion Although the pattern and the degree of intensity of THAD and AC severity were not related, THAD might be useful in diagnosing AC. Thus, THAD should be considered a diagnostic criterion for AC.